Growing Media Combination Improve Plant Growth and Results of Eggplant (Solanum melongena L) in Hydroponic Culture Duck Bucked System - Iskandar Umarie (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2019)
Today business eggplant still give a pretty good market opportunities, especially to meet the demand of the domestic market. Hydroponics is a way of cultivating plants without using soil, but the use of media such as rice husk, sawdust, fine sand, bricks, coco, and more.The research objective, to get the best medium composition hydroponic cultivation of eggplant Duck Bucked system. Research conducted at the Laboratory of Urban Agriculture Faculty of Agriculture, University of Muhammadiyah Jember, December 2018 to April 2019, indesigned randomized block design factorial arranged secaranon repeated 3 times. that is A (Charcoal chaff), S (Sawdust), B (Bricks), AS ( Charcoal and Sawdust Husk) with 3: 1, AB (Charcoal Husk and Bricks) with 3: 1, BA (Bricks and Charcoal husks with 3:1, BS (Bricks and Sawdust) with 3:1, SA (Sawdust and Charcoal husks) with 3:1, SB (Sawdust and bricks) with 3:1), ASB (Charcoal Sawdust Husk and Bricks) with 1:1:1. The result showed treatment of growing media composition of the substrate affects the vegetative growth of plant height at 45 and 60 days after planting, biomass wet weight, dry weight biomass, root fresh weight and root dry weight, the best substrate media broken bricks. While composition of the substrate growing media influence on the amount of fruit harvest and to all III-V substrate media best media substrate broken bricks. Conclusions broken bricks media substrate is a substrate of the best media for eggplant plants in the hydroponic system Duck Bucked.